The Effect of Capital Intensity and Leverage on Accounting Conservatism in Basic Industry and Chemical Sector Manufacturing Companies Listed on the IDX in 2019-2023 - Gitta Destalya Adrian Nova; Yulitiawati; Sindy Safitri; Anis Feblin; Eka Meiliya Dona; Hasiatul Aini (Universitas Indo Global Mandiri, 2026)
A company’s financial statements reflect the effectiveness of management in managing the company’s resources. Management may choose which accounting techniques to use in preparing financial statements. One such technique is the principle of accounting conservatism. The application of accounting conservatism in the presentation and disclosure of financial information is important and necessary due to a tendency among management to present financial statements with an overstated bias that can mislead users.This study aims to determine the effect of capital intensity and leverage on accounting conservatism in manufacturing companies in the basic and chemical industry sectors listed on the IDX in 2019-2023. This study uses a quantitative approach with secondary data sources. The population is 365 company annual report data obtained from 73 manufacturing companies in the basic and chemical industry sectors. The sampling technique uses purposive sampling of 95 annual report data companies obtained from 19 manufacturing companies in the basic and chemical industry sectors. The analysis technique uses multiple linear regression with hypothesis testing, namely partial test (t test) and simultaneous test (f test). The results in this study indicate partially that the capital intensity variable (X1) has a significant negative effect on accounting conservatism (Y) and the leverage variable (X2) has no effect on accounting conservatism (Y). Capital intensity and leverage variables simultaneously affect accounting conservatism. The coefficient of determination (R square) value is 0.116 or 11.6% while the remaining 88.4% is due to other factors. Keywords: Capital Intensity, Leverage, Accounting Conservatism